2008
DOI: 10.1196/annals.1405.035
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐to‐Cell Signaling at the Neuromuscular Junction

Abstract: The extracellular matrix at the neuromuscular junction plays many roles. The matrix plays a structural role in that it maintains the spatial relationship between the muscle cell, Schwann cell, and presynaptic motor neuron. The matrix also plays a role in cell-to-cell signaling. The most studied member of this group is the heparan sulfate proteoglycan, agrin. Agrin is an integral member of the synaptic matrix, and it plays the pivotal role of instructing the muscle cell to aggregate acetylcholine receptors (ACh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Antibodies to MMP3 recognize molecules concentrated at the synapses of frog NMJs. NMJs in MMP3 null mutant mice have increased junctional folds and AChR aggregates [40]. The role of MMP3 in NMJ stabilization has not been directly tested, but MMP3 depletion prevents motor endplate degradation following traumatic peripheral nerve injury in KO mice.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…Antibodies to MMP3 recognize molecules concentrated at the synapses of frog NMJs. NMJs in MMP3 null mutant mice have increased junctional folds and AChR aggregates [40]. The role of MMP3 in NMJ stabilization has not been directly tested, but MMP3 depletion prevents motor endplate degradation following traumatic peripheral nerve injury in KO mice.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…laminins) and ECM receptors (e.g. integrins, dystroglycan) (Nicholson et al, 2005; Lluri et al, 2006; Page-McCaw et al, 2007; Murphy and Nagase, 2008; Werle, 2008). Such cleavage changes receptor-binding affinities during synaptic development and modulation (Wlodarczyk et al, 2011) and regulates both synaptogenesis and the synaptic modulation underlying behavior (Ethell and Ethell, 2007; Agrawal et al, 2008), with defects linked to synaptic disorders including Fragile X syndrome (Bilousova et al, 2009).…”
Section: Organization and Remodelling Of Nmj Synapse Ecmmentioning
confidence: 99%
“…While the manifestations of deficits in the active component are readily diagnosed and unmistakably detrimental to daily function (NIMSD Consortium, 1996; Fried et al, 2001), analogous alterations in the passive component are less understood. This apparent lack of information should not imply that passive skeletal muscle stiffness does not play a key role in skeletal muscle growth, metabolism, or function – as it is integral for all three (Jaspers et al, 1999; Kjaer, 2004; Tatsumi et al, 2006; Werle, 2008). Numerous in vitro studies have identified the connective tissue network of collagen within the extracellular matrix (ECM) as a key contributor to passive stiffness in a variety of skeletal muscles (Bensamoun et al, 2006; Borg and Caulfield, 1980; S.…”
Section: Introductionmentioning
confidence: 99%
“…H. Brown et al, 2012; Rowe et al, 2010). It is becoming increasingly apparent that the ECM is vital for mechanotransduction, as well as muscle growth and adaptation (Jaspers et al, 1999; Kjaer, 2004; Tatsumi et al, 2006; Werle, 2008). Later research indicates that passive stiffness may also play a role in muscle performance and adaptation to exercise (Fouré et al, 2011).…”
Section: Introductionmentioning
confidence: 99%